ANALISIS PERBANDINGAN KINERJA PORTOFOLIO OPTIMAL MODEL MARKOWITZ (Studi Kasus Saham Indeks IDX Growth30 & Indeks JII70 Pada BEI Periode 2020-2021) - Diky Albarado; Andewi Rokhmawati; Haryetti Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the difference in the coefficient of variation of thestock portfolio on the IDX GROWTH30 and JII 70 indices during the periodAugust 2020 - July 2021 using the Markowitz model. The research method used inthis study is a comparative method. This study uses secondary data. Thepopulation in this study are 10 stocks that are members of the IDX GROWTH30and JII 70 indexes on the IDX for the period August 2020 - July 2021. Thesampling method uses purposive sampling technique, obtained 16 stocks from theIDX GROWTH30 index and 58 stocks from JII 70. Statistical analysis used in thisstudy is the data normality test, while the hypothesis testing used is the MannWhitney Test and data processing using LINGO software, SPSS 26.0 andMicrosoft Excel as auxiliary tools. The test results in this study indicate that thereare differences in the coefficient of variation of the stock portfolio between theIDX GROWTH30 index and the JII 70 index. Then there are 7 stocks that make upthe optimal portfolio of IDX GROWTH30 and 14 stocks that make up the portfolioon the JII 70 index. Keywords: Optimal portfolio, Markowitz Model, IDXG index 30, JII index 70,Minimize risk.